Analysing the financial efficiency of use of water and energy saving systems in single-family homes. (10th May 2017) - Stec, Agnieszka; Kordana, Sabina; Słyś, Daniel
Abstract: Increasing demand for water and energy sources, accompanied by continued increases in the prices of these sources, has been observed worldwide. This has resulted in the need to seek alternative sources. In response to this statement, a cost-effective analysis has been carried out to enable the use of selected systems to reduce demands for potable water and natural gas used for heating in single-family homes. The study includes the Drain Water Heat Recovery System, Gray Water Harvesting System and Rainwater Harvesting System. The Life Cycle Cost methodology has been applied as a tool for the analysis. Depending on the number of users and rate of piped water consumption the determined Life Cycle Cost indicator ranged from €11519 to €19678. The study has shown that the highest life cycle cost are characteristic of the graywater recycling variant. In circumstances where water consumption in homes for purposes of showering and toilet flushing exceeded 300 L per day, the most cost-effective is the option that combines all systems analyzed. The most preferred, in the other cases was the use of Rainwater Harvesting System. The sensitivity analysis carried out has also shown that costs changes associated with building water supply and sewerage facilities has had the greatest impact on life cycle costs of each solution. The analysis have shown that the systems under consideration could serve as alternatives for traditional installations. Their use has resulted in reductions in the consumption of fossil fuels and natural water resources, thus contributing to environmental improvements. Highlights: Systems allowing water and energy consumption reduction are described. Parameters of systems usage have a significant influence on its profitability. Conducted analysis confirms profitability of the selected systems.